Measurement of (B)over-bar(0)-> D-(*()0)(K)over-bar(()*()0) branching fractions - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2006)
We report a measurement of the exclusive B+ meson decay to the final state D-s K+π+ using 520 × 106B ̄B pairs collected near the γ(4S) resonance, with the Belle detector at the KEKB asymmetric-energy e+e- collider. Using the D-S → Ø- decay mode to reconstruct D- s mesons, we obtain the branching fraction B(B+ → D-s K+π+) = (1.77+0.12-0.12(stat)±0.16(syst) ±0.23(B))×10-4. We also present preliminary results of a study of the two-body DsK, Dsπ and Kπ subsystems observed in this final state.